Industrial robot adoption and corporate financial restatements: evidence from China - Zhao, Jing; Saidin, Saidatunur Fauzi; Atqa, Asna Abdullah; Chen, Lin (Transformations In Business & Economics, 2026)
As a core technology driving the digital transformation of manufacturing, industrial robots have attracted growing scholarly interest in terms of their economic consequences within corporate governance research. However, existing literature offers limited systematic theoretical insight into how the adoption of industrial robots influences corporate financial restatements. To explore the relationship between industrial robot adoption and corporate financial restatements, drawing on information asymmetry and managerial myopia theories and using a sample of Chinese A-share manufacturing listed firms from 2010 to 2022, the impact mechanism of industrial robot adoption on corporate financial restatements is analyzed. Results reveal that: industrial robot adoption significantly reduces the likelihood of financial restatements, a result that remains robust under a series of sensitivity tests; (2) the reduction is primarily achieved through enhanced information quality and improved internal governance, whereas the risk-taking channel exhibits a masking effect; and (3) the restraining effect of robot adoption on financial restatements is more pronounced in non-state-owned enterprises, firms in more competitive industries, labor-intensive firms, and those facing more pessimistic analyst forecasts. The conclusions extend the theoretical boundaries of research on the economic consequences of industrial robots and offer valuable insights for policymakers seeking to advance smart manufacturing and improve the information environment of capital markets.